Psychological distress as a predictor of emotional exhaustion in university students: A cross-sectional study - Estrada-Araoz, Edwin Gustavo (2024)
Background: This research is predictive and aims to determine if psychological distress predicts emotional exhaustion in a sample of university students from the Peruvian Amazon. Methods: The study employed a quantitative approach with a non-experimental predictive cross-sectional design. The sample consisted of 163 students who completed the Psychological Distress Scale and the Emotional Exhaustion Scale, both instruments with adequate levels of validity and reliability. Results: Initially, it was found that the predominant level of psychological distress and emotional exhaustion was moderate. Furthermore, it was determined that both variables correlated directly and significantly (r= 0.549; p<0.05). Additionally, simple linear regression analysis demonstrated a good fit of the model (F= 117.055; p<0.05), where psychological distress (β= 0.549; p<0.05) explained 29.8% of the total variance in emotional exhaustion. Conclusions: It was concluded that psychological distress predicts emotional exhaustion in a sample of university students from the Peruvian Amazon. This suggests that higher levels of psychological distress are directly associated with increased levels of emotional exhaustion among university students. Therefore, it is recommended to develop psychological and emotional support programs within universities, focusing on coping techniques and stress reduction tailored to the cultural and environmental specificities of the context.